2019
DOI: 10.1371/journal.pone.0197644
|View full text |Cite
|
Sign up to set email alerts
|

Identification, structure-activity relationship and in silico molecular docking analyses of five novel angiotensin I-converting enzyme (ACE)-inhibitory peptides from stone fish (Actinopyga lecanora) hydrolysates

Abstract: Stone fish is an under-utilized sea cucumber with many health benefits. Hydrolysates with strong ACE-inhibitory effects were generated from stone fish protein under the optimum conditions of hydrolysis using bromelain and fractionated based on hydrophobicity and isoelectric properties of the constituent peptides. Five novel peptide sequences with molecular weight (mw) < 1000 daltons (Da) were identified using LC-MS/MS. The peptides including Ala-Leu-Gly-Pro-Gln-Phe-Tyr (794.44 Da), Lys-Val-Pro-Pro-Lys-Ala (638… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 53 publications
0
42
0
Order By: Relevance
“…Furthermore, some studies have indicated that peptides with HAAs at the C-and N-terminals might enhance ACEI activity. 31,32 In this study, the IC 50 value of the tetrapeptide LPYY was determined to be 116.26 mM. The inhibitory activity of LPYY may be attributed to its high ratio of HAA residues as well as its hydrophobic-hydrophilic-hydrophobic structure in the peptide sequencethe highly HAAs Leu and Tyr are located at the Nand C-terminals, respectively, whereas the hydrophilic amino acid Pro occupies the second position.…”
Section: Structure-activity Relationships Of Acei Peptidesmentioning
confidence: 80%
“…Furthermore, some studies have indicated that peptides with HAAs at the C-and N-terminals might enhance ACEI activity. 31,32 In this study, the IC 50 value of the tetrapeptide LPYY was determined to be 116.26 mM. The inhibitory activity of LPYY may be attributed to its high ratio of HAA residues as well as its hydrophobic-hydrophilic-hydrophobic structure in the peptide sequencethe highly HAAs Leu and Tyr are located at the Nand C-terminals, respectively, whereas the hydrophilic amino acid Pro occupies the second position.…”
Section: Structure-activity Relationships Of Acei Peptidesmentioning
confidence: 80%
“…Among commonly used in silico methods, molecular docking permits researchers to evaluate the interaction between peptides and complex proteins, in order to predict the binding free energy values and the putative binding modes [ 41 ]. A similar work-flow has been applied for discovering novel ACE inhibitory peptides from stone fish protein hydrolysates [ 42 ]. Besides the molecular docking study, here also MD simulations were performed in order to evaluate the stability of the complex during a specified simulation time, improving greatly the accuracy of the predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Docking is a computer-based method that predicts the affinity and binding conformation of a small molecule ligand (an inhibitor) to the appropriate target binding site (an enzyme) in order to determine and evaluate the hydrogen bond, hydrophobic interaction, electrostatic interactions, Van der Waals interaction force and total energy between peptide and ACE [14,15]. Recently, in silico molecular docking has been used to study the interaction between inhibitory peptides and ACE in pistachio hydrolysate [15], Salmo salar [16], milk protein [17], hemp seed [12] and stone fish hydrolysates [18].…”
Section: Introductionmentioning
confidence: 99%